2008
DOI: 10.1016/j.neuroscience.2007.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory effects of human immunodeficiency virus 1 Tat on cultured rat cerebral cortical neurons

Abstract: HIV-1 Tat protein is one of the neurotoxins involved in the pathogenesis of HIV-1-associated neuronal disorders. Combined electrophysiological and optical imaging experiments were undertaken to investigate whether HIV-1 Tat30-86, herein referred to as Tat30-86, acted directly or indirectly via the release of glutamate or both and to test its effect on the properties of spontaneous quantal events in cultured cortical neurons. Whole-cell patch recordings were made from cultured rat cortical neurons in either cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 41 publications
6
60
1
Order By: Relevance
“…Measurement of Membrane Potential-The relative changes in membrane potential of single cardiomyocytes were evaluated using bis-(1,3-dibutylbarbituric acid) trimethine oxonol, bis-(1,3-dibutylbarbituric acid) trimethine oxonol, a slow-response, voltage-sensitive dye, as described previously (32)(33)(34). Upon membrane hyperpolarization, the dye concentrates in the cell membrane, leading to a decrease in fluorescence intensity, whereas depolarization induces the sequestration of the dye into the cytosol, resulting in an increase of the fluorescence intensity (35).…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of Membrane Potential-The relative changes in membrane potential of single cardiomyocytes were evaluated using bis-(1,3-dibutylbarbituric acid) trimethine oxonol, bis-(1,3-dibutylbarbituric acid) trimethine oxonol, a slow-response, voltage-sensitive dye, as described previously (32)(33)(34). Upon membrane hyperpolarization, the dye concentrates in the cell membrane, leading to a decrease in fluorescence intensity, whereas depolarization induces the sequestration of the dye into the cytosol, resulting in an increase of the fluorescence intensity (35).…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of Membrane Potential-Bis-(1,3-dibutylbarbituric acid) trimethine oxonol (DiBAC 4 (3), Invitrogen), a slow response voltage-sensitive dye, was used to assess relative changes in membrane potential of single cells, as described previously (26). Upon membrane hyperpolarization, the dye concentrates in the cell membrane, leading to a decrease of fluorescence intensity, whereas depolarization results in a sequestration of the dye into cytosol and is associated with an increase in the fluorescence intensity (27).…”
Section: Methodsmentioning
confidence: 99%
“…Several viral proteins are neurotoxic, including the envelope glycoprotein, gp120, an essential mediator of virus entry into host cells, and the transactivator of transcription (Tat), an activator of transcription of the viral genome (Jones et al, 1998;Haughey and Mattson, 2002). Tat excessively increases Ca 2+ influx in neurons, including pyramidal neurons (PN) of the medial prefrontal (mPFC) (Brailoiu et al, 2008;Napier et al, 2014), by prolonging Ca 2+ potentials mediated by L-type Ca 2+ channels (Lchannels) that profoundly enhances firing (Napier et al, 2014). In vitro studies have demonstrated that neurotoxic effects of gp120 and Tat can be enhanced by other viral proteins (Nath et al, 2000) and cocaine (Aksenov et al, 2006).…”
Section: Hivmentioning
confidence: 99%